Science Teachers’ Perception About Laboratory Activity on Mixture Separation Topics - Reni Meidayanti; Noor Fadiawati; Chansyanah Diawati (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The design of this research is survey research. This study aimed to explore seventh-grade science teachers’ perception of laboratory activity on mixture separation topics and match them with available evidence from learning document. The sample comprised 10 seventh grade science teachers, purposively sampled from seventeen teachers. Questionnaires and interview guidelines were used to collect data. The results show that while teachers’ perceptions of mixture separation topics in science classrooms are inadequate. Caused, there was a mismatch between teachers’ perceptions, learning document, and what was taking place in the science classroom. The study may inform teachers’ performance in teaching mixture separation topics in science. It is recommended that teacher on learning should be used to practice worksheet and assessment of laboratory activity, as most of the teachers do not record marks regularly for laboratory activity. Furthermore, laboratory activity prepared by the teacher should be arranged in a lesson plan and practice schedules.